(untitled) (Research, Society and Development, 2021)
Objective: To review the literature on User Embracement and adolescent health care. Methodology: This is a literature review, with a systematized search. The databases consulted were Virtual Health Library (VHL) and Pubmed and inclusion criteria: studies on the subject; complete and available works; languages Portuguese, English or Spanish; papers published from 2004; all types of study, except review. The content of the papers was read in depth and the categories of analysis were defined. Results: The search for the descriptors resulted in 713 studies, which after reading the title, were reduced to 49. After reading the abstracts, 15 papers were selected for full reading. Of these, 9 met the study criteria. A low demand of adolescents for health services was found. Conditions were identified in health services that interfere in the health care of adolescents. These conditions were classified as macro, meso and micro dimension. The macro dimension refers to the conditions of the care model. The meso dimension covers the structural conditions of adolescent care and training of health professionals. The micro dimension concerns interpersonal relationships between adolescents and health professionals. Conclusion: The results of this study suggest that adolescent health care requires initiatives that respond to its specificities and User Embracement is fundamental to bring adolescents closer to care, as it humanizes, creates bonding, respect for individuality and autonomy.